Technology Transformation and Its Impact on Lecturerâ€™s Performance - Arifin, S.; Sukmawidjaya, M. (JPI (Jurnal Pendidikan Indonesia), 2020)
The interest to do this research is to investigate the impact of technology transformation on the lecturer's performance. The terms technical performance in this research are divided into five (5) indicators: engaging and empowering learning, and teaching with technology, leadership, accommodation (syllabus and lesson scheme), and infrastructure provided by the campus. The findings indicate that many lecturers have a lack of knowledge in technology transformation. Â However, all lecturers must have it for the teaching and learning process in the 21st-century. The research methods used were descriptive analysis, observations, quantitative and semi-structured qualitative research, and the questionnaires done using Google Form. There were sixty-four (64) respondents in this research. The result shows that the use of technology proves its significant impact on the lecturer's performance.Â